2019
DOI: 10.1038/s41436-018-0387-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary research uses of residual newborn screening dried bloodspots: a scoping review

Abstract: Purpose Residual newborn screening dried bloodspots (DBS) are a valuable resource for research but the extent, type, and nature of uses are unknown. The objective of this research was to systematically review the published literature about secondary research uses of residual DBS using a scoping review protocol. Methods A total of 654 publications meeting the inclusion criteria with a 94% interrater reliability were identified. A coding template was created with input fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…DBS represent an invaluable resource for research aimed at elucidating the underlying etiology of human diseases, including birth defects, metabolic disorders, and congenital heart defects, and may be particularly suitable for newly available methods for whole genome sequencing (WGS). 1,6,12,13 Additionally, for infants who die shortly after birth, DBS may be resourced for investigation of the molecular cause of death. [14][15][16] DBS have numerous advantages over whole blood samples, including ease of transport, potential for storage at room temperature, cost effectiveness and feasibility of long-term storage without degradation of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…DBS represent an invaluable resource for research aimed at elucidating the underlying etiology of human diseases, including birth defects, metabolic disorders, and congenital heart defects, and may be particularly suitable for newly available methods for whole genome sequencing (WGS). 1,6,12,13 Additionally, for infants who die shortly after birth, DBS may be resourced for investigation of the molecular cause of death. [14][15][16] DBS have numerous advantages over whole blood samples, including ease of transport, potential for storage at room temperature, cost effectiveness and feasibility of long-term storage without degradation of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…A scoping review of publications from 1973 to 2017 on research using dried blood spots from new-born screening programmes, revealed that 55% of studies originated outside the United States, with 7.4, 7.2, 6.1, 5.5, and 5.0%, respectively from the United Kingdom, Denmark, Italy, Germany, and Sweden ( 15 ). An estimated 37.5% of samples from the Danish New-born Screening Biobank, established in 1982, have appeared in publications of secondary research, with the first paper being published in 1991 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DBS biospecimens are similar to other clinical biospecimens, and can be used for a variety of clinical and research activities. As noted in the literature, a wide range of valuable research has been conducted using DBS (Rothwell et al 2019;Maschke 2008).…”
Section: Introductionmentioning
confidence: 99%